Improving Public Services: Public Administration Reform in Northern Ireland - Knox, Colin; Carmichael, Paul (Journal of Social Policy, 2004)
The devolved government in Northern Ireland set about the task of putting in place ‘a modern and effective system of public administration that can deliver high quality public services to our citizens’. It did so through a review of public administration launched in June 2002. This paper offers a formative evaluation of the quest to improve the quality of public services, now being taken forward by a British minister since the suspension of devolution. It argues that the review is being driven by institutional concerns and is devoid of a public service modernising agenda. Additionally, it contends that how people in Northern Ireland perceive public services is contingent on their views on its constitutional status (Direct Rule or devolved government) which, in turn, is linked to their support for the Belfast (Good Friday) Agreement, rather than the performance of public bodies. As a consequence, the reforms may result in little more than institutional tinkering with doubtful impact on the quality of public services
Keywords: Northern Ireland; Public Administration